APPLICATION OF INTUITIONISTIC FUZZY SETS IN RESEARCH QUESTIONNAIRE - Ejegwa, P. A. (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
An application of intuitionistic fuzzy sets in research questionnaire construction, filling, analysis, and interpretation is given. Respondentsâ€™ decision is obtained assuming questionnaire is distributed among respondents. The respondentsâ€™ decision is converted into intuitionistic fuzzy values, analysed, and from which interpretation is drawn.Â Keywords:fuzzy sets, intuitionistic fuzzy sets, questionnaire, respondents, sociometry.